2015
DOI: 10.1038/pr.2015.214
|View full text |Cite
|
Sign up to set email alerts
|

Beyond screening: a review of pediatric primary care models to address maternal depression

Abstract: Depression is one of the most debilitating chronic disorders in the United States, affecting 15 million children in homes with depressed mothers, many of whom endure household chaos, inconsistent nurturing, inadequate safety practices, and harsh discipline. Depressed mothers are under diagnosed and undertreated, yet there is broad consensus about the importance of identifying and managing maternal depression, as reflected in recommendations by pediatric and obstetric professional organizations to routinely scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Recent reviews have identified several models for managing PD in pediatric settings. 18,19 Care strategies were highly similar across both pediatric and adult primary care settings. A ''screen and manage'' approach was common within pediatric models, with varying degrees of maternal depression management within the practice where screening occurred.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent reviews have identified several models for managing PD in pediatric settings. 18,19 Care strategies were highly similar across both pediatric and adult primary care settings. A ''screen and manage'' approach was common within pediatric models, with varying degrees of maternal depression management within the practice where screening occurred.…”
Section: Introductionmentioning
confidence: 99%
“…There is currently no well-designed clinical trial that shows a benefit of depression screening alone 17 ; positive outcomes, however, were found to be associated with screening when enhanced depression care was available for postpartum women who screen positive. [18][19][20] Existing international guidelines thus differ in their recommendations. Both the U.K. National Institute for Health and Care Excellence and the Canadian Task Force on Preventive Healthcare's guidelines recommend against formal screening for depression during the perinatal period.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations